Headache in progressive facial hemiatrophy (Parry-Romberg syndrome): A paradigmatic case and systematic review of the literature. (April 2022) - Foiadelli, Thomas; Rossi, Alessandra; Trabatti, Chiara; Spreafico, Eugenia; Santi, Viola; Orsini, Alessandro; Verrotti, Alberto; Savasta, Salvatore
Background: Parry-Romberg syndrome is a neuro-cutaneous disease characterized by progressive hemifacial atrophy. Although common, headache in this population is scarcely reported in the literature. Objective: To evaluate the clinical features of headache in pediatric and adult patients with Parry-Romberg syndrome, and to discuss diagnostic and treatment approaches of headache in Parry-Romberg syndrome. Methods: We conducted a systematic review in accordance with PRISMA guidelines. We searched the MEDLINE database to identify eligible studies and identified patients with Parry-Romberg syndrome and headache. We further reported a paradigmatic case with a complex headache disorder and described its management and outcome. Results: We identified 74 articles, 41 of which were included in the analysis. A total of 52 patients (55.8% female) were included for data analysis. The main age at onset of headache was 20 years (SD 15.2; range 3–56). A diagnosis of migraine was made in 53.9%. Abnormal brain imaging was found in 82.2% of patients. Conclusion: Long-term follow-up of patients is required, because headache may develop (and evolve) at any time over the course of the disease. Primary and secondary headaches often co-occur in patients with Parry-Romberg syndrome. Further research into the underlying etiopathogenesis and therapeutic targets would be recommended.